Pengaruh Model Pembelajaran PJBL (Project Based Learning) Terhadap Kemampuan Berfikir Kreatif Siswa Biologi Sekolah Menengah Atas: A Literature Review - Alda Deria; Muhyiatul Fadilah; Izzatul Kamilatun Nisa; Aprilla Fortuna; Bagas Fajriansyah; Putri Salsabila; Ramos Mardiansyah; Fiana Amara Alika; Lismita Lismita; Upik Junita (PAKAR Pendidikan, 2023)
Education is an effort made by the government to create an atmosphere in the learning process for students to be active in building their potential. In the educational process, students are expected to have religious values, be able to control themselves, personality, intelligent, intellectual, moral, and skilled. Students in schools are asked to have 21st-century skills, namely the appearance known as "4C", one of which is creative thinking skills. To realize this, the role of teachers in schools is needed as educators. In the learning process, the learning model needs to be considered by a teacher for the learning objectives to be achieved. The learning model is (Project Based Learning) which reveals whether the learning model influences the creative thinking of high school biology students, researchers conduct literature reviews related to this. The method in this study is a literature review method, namely analyzing relevant articles with a descriptive type qualitative approach by including the keywords "Project Based Learning" and "creative thinking ability". The result of this literature review is that the PJBL (Project Based Learning) learning model has a significant effect on the ability to think in high school biology class students. In addition to the syntax of the PJBL (Project Based Learning) model which can require students to solve problems in the form of projects so that students can think creatively, other things also support the use of the PJBL (Project Based Learning) learning model such as the use of interesting media-assisted or the use of supporting student worksheets.